RESEARCH FOR ESTABLISHING A SET OF CRITERIA FOR ASSESSING THE INTELLIGENCE LEVEL OF MANUFACTURING FACTORIES - Pham Thi Hoai Thu; Tran Doan Hieu; Tran Son Ninh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2023)
Along with the development of science and technology, building smart factories is a trend that is spreading strongly all over the world, including Vietnam. There are currently many inconsistent interpretations and assessments of how smart a factory is. By combining published worldwide studies and expert opinion surveys, the authors recommended a set of criteria for assessing the intelligence level of manufacturing factories using the Analytical Hierarchy Process (AHP) technique. The set of criteria serves as a tool for managers to design smart strategies and establish the necessary degree of smart investment in each development stage to both maintain production and company in the present while allowing for future growth. Code: 23011701